Deep learning as phase retrieval tool for CARS spectra - Houhou, Rola; Barman, Parijat; Schmitt, Micheal; Meyer, Tobias; Popp, Jürgen; Bocklitz, Thomas (Optics Express, 2020)
Finding efficient and reliable methods for the extraction of the phase in optical measurements is challenging and has been widely investigated. Although sophisticated optical settings, e.g. holography, measure directly the phase, the use of algorithmic methods has gained attention due to its efficiency, fast calculation and easy setup requirements. We investigated three phase retrieval methods: the maximum entropy technique (MEM), the Kramers-Kronig relation (KK), and for the first time deep learning using the Long Short-Term Memory network (LSTM). LSTM shows superior results for the phase retrieval problem of coherent anti-Stokes Raman spectra in comparison to MEM and KK.
CRIS-Team Scopus Importer:2023-04-20